The Use of Bicomat and Tithonia Compost on Chemical Properties of Post-Mining Group-C Soil After Bok Choy Cultivation - Lidwina Mita Sari; Amnawadi; Choky Afrizal Maulana; Filipus Rendi; Yoseph Frinadetz Ragan Kedang; Retno Wilujeng; Hidayati Karamina; I Made Indra Agastya (Acta Solum, 2026)
In mining areas, improper soil management frequently leads to soil degradation and the depletion or loss of N, P, and K nutrients. Bicomat is known as an effective amendment for improving physical properties in the short term, whereas its effects on chemical properties generally become evident only in the long term. The purpose of this study was to determine the effect of combining Bicomat and Tithonia compost on the chemical properties of Group-C post-mining soil after planting mustard greens. This study was conducted from October to December 2024 at the Science Technopark of Tribhuwana Tunggadewi University, Malang City, at an altitude of approximately 450 meters above sea level. The study employed a non-factorial Randomized Block Design (RBD) with 8 treatments and 3 replications. The tested treatments consisted of: KT1 (Non-Mining Soil Control), KT2 (Group-C Mining Soil Control), T1P1B1 (Soil 1, 200 g fertilizer, 10 t ha⁻¹ Bicomat), T1P1B2 (Soil 1, 200 g fertilizer, 20 t ha⁻¹ Bicomat), T1P2B2 (Soil 1, 300 g fertilizer, 20 t ha⁻¹ Bicomat), T2P1B1 (Soil 2, 200 g fertilizer, 10 t ha⁻¹ Bicomat), T2P1B2 (Soil 2, 200 g fertilizer, 20 t ha⁻¹ Bicomat), and T2P2B2 (Soil 2, 300 g fertilizer, 20 t ha⁻¹ Bicomat). The results showed that the combination of Bicomat and compost had a significant effect on improving the chemical properties of the Group-C post-mining soil. The best results for nitrogen, phosphorus, and potassium were obtained from treatment T1P2B2, while treatments T1P1B1 and T2P1B1 yielded the best results for organic C.